The Mediating Effect Of Shariah Supervisory Board On Management Control System And Performance Of Islamic Banks In Indonesia: Competitive Strategy As Moderator - Lesmana, Sukma (2024)
This study aimed to investigate the impact of the Shariah Supervisory Board as a mediator and competitive strategy as a moderator on the relationship between the management control system and the performance of Islamic banks in Indonesia. The management control system of Islamic banks in Indonesia was studied based on Simon's levers of control, and the performance was evaluated using the Maqasid Shariah concept. The study included 128 respondents from 32 Islamic banks registered under the Financial Services Authority (OJK), and the hypothesis testing was conducted using PLS-SEM with Warppls software version 8.0. The results indicated that the boundary system had a positive and significant impact on the performance of Islamic banks in Indonesia. Furthermore, the Shariah Supervisory Board acted as a mediator in the relationship between the boundary system and the performance of Islamic banks, and the interactive control system. All the Islamic banks in Indonesia utilized low-cost strategies that facilitated the implementation of belief and boundary systems. The implications of this research confirm that the management control system will improve the performance of Islamic banks with the support of the functions and roles of the Shariah supervisory board. The study also demonstrated that integrating of agency, stewardship, and stakeholder theories influenced corporate governance implementation in Islamic banks.